Hei-tag: a highly efficient tag to boost targeted genome editing - Thumberger, Thomas; Tavhelidse-Suck, Tinatini; Gutiérrez Triana, José Arturo; Medert, Rebekka; Cornean, Alex; Welz, Bettina; Freichel, Marc; Wittbrodt, Joachim (bioRxiv beta, 2021)
Precise, targeted genome editing by CRISPR/Cas9 is key for basic research and translational approaches in model and non-model systems1. While active in all species tested so far, editing efficiencies still leave room for improvement. To reach its target, the bacterial Cas9 needs to be efficiently shuttled into the nucleus as attempted by fusion of nuclear localization signals (NLSs) to the Cas9 protein2. Additional domains such as FLAG- or myc-tags are added for immediate detection or straight-forward purification3. To avoid steric hinderance impacting on activity, amino acid linkers are employed connecting Cas9 and additional domains. - We present the ‘hei-tag (high efficiency-tag)’, boosting the activity of the wide variety of CRISPR/Cas genome editing tools. The addition of the hei-tag to Cas9 or a C-to-T base editor dramatically enhances the respective targeting efficiency in model systems ranging from fish to mammals, including tissue culture applications. This allows to instantly upgrade existing and potentially highly adapted systems as well as establish novel highly efficient tools.
Gesehen am 27.02.2024